PROMOTING AUTONOMOUS LEARNING THROUGH âHOT POTATOESâ - Gendroyono, Gendroyono (ELTICS Journal, 2014)
This study was designed to investigate the role of âHot Potatoesâ in promoting autonomous learning of the English education students at Muhammadiyah University of Yogyakarta. This study was conducted on some reasons: first, autonomous learning is very significant in the success of learnersâ learning, and to make the learners implement autonomous learning is quite tricky. Second, the use of Hot Potatoes as the software is very simple and fun to publish any education materials online, and as a result, the students like the program. Therefore, it is very challenging for the teacher to find a way to promote autonomous learning to the students through the use of a simple education software called âHot Potatoesâ. The study was aimed at exploring the roles of Hot Potatoes in English teaching and learning. Further, it also explored the advantages of the Hot Potatoes in developing the studentsâ ability or habit in having autonomy in their learning. This research was a qualitative case study in nature since it dealt with a holistic description. The setting of the research was Muhammadiyah University of Yogyakarta with 10 students who have implemented Hot Potatoes in designing teaching materials for them to use at schools. The procedure to collect the data was through questionnaires and interviews with the participants. In analyzing the data, the researcher first categorized the data gained from the questionnaires and then extracted the information from the data collected through the interview process. The data were then grouped into categories and interpreted in accordance with the research questions. The study found that students first had awareness to be better in mastering English due to their online publishing the teaching materials developed with Hot Potatoes. They were aware that by publishing materials online, people all around the globe would have a chance to stop by and read the materials. This awareness led them to learn by themselves on the grammar of the sentences they wrote. As a result, they started looking up grammar books to check if the grammar was appropriate or not. The same process also happened to the choice of words and the spelling of words used in the teaching materials they developed. They checked and rechecked until they were sure of the correctness of the dictions and the spelling. The last but not least is about the cultural issue in the sentences. It dealt with the appropriateness of the sentences they make due to native speakersâ cultural background. Therefore, the writer concluded that the use of Hot Potatoes promoted autonomy in studentsâ learning. Keywords: Autonomous learning, Hot Potatoes, Studentsâ Awareness, online publishing